Comparison of O2 saturation, heart and respiratory rate following injection of vasoconstrictor containing anesthetic (lidocaine 2%) and without vasoconstrictor anesthetic (Mepivacaine) - Bayat M.; Zaeri F.; Sadatnia F (Tehran University of Medical Sciences, 2005)
Background and Aim: Along with higher usage of dental local anesthesia with risks to people health together with their positive role, the important goal of dentistry, patients' health, has been stressed repeatedly nowadays. This study was conducted to compare O2 saturation, respiratory rate and heart rate of patients following injection of anesthetic containing vasoconstrictor (lidocaine 2%) and without vasoconstrictor (Mepivacaine). Materials and Methods: This experimental study was conducted on 32 healthy humans (16 females and 16 males) with 25-50 years age range and no history of drug usage. Cases were classified into two matched groups. O2 saturation, heart and respiratory rate were recorded before extraction of a mandibular posterior tooth. In the first group, 3.6 ml lidocaine 2% with 1:80,000 epinephrine and in the second group Mepivacaine 3% was injected, using inferior alveolar dental nerve block with aspiration. Variables were measured and recorded. Tooth extraction was performed and the mentioned variables were recorded again. Data were analyzed with SPSS software using t and Paired t-test with P<0.05 as the limit of significance. Results: After injection of lidocaine, the heart rate was increased (12.25±1.75 bpm), and the time to reach the maximum rate was 64.75±11.26 seconds. After extraction of tooth, heart rate in both groups was increased not considering the type of injection. Conclusion: The study showed that the injection of lidocaine (containing epinephrine) in patients without contraindication has no risk. Also, possible increase in heart rate is not risky and is not associated with O2 saturation decrease and respiratory interruption.